Efektivitas Pendirian Akademi Komunitas dalam Mendukung Masterplan Percepatan dan Perluasan Pembangunan Ekonomi Indonesia (MP3EI) - Ikhya Ulumudin (Jurnal Pendidikan dan Kebudayaan, 2015)
This study is aimed at figure out the suitability of study programs in the community college to the region’s potential and the level of interest of senior secondary school graduates in continuing to community college in order to support the Master Plan for the Acceleration and Expansion of Indonesia’s Economic Development (MP3EI) program. The method used was survey, while the data and information were gathered through Focus Group Discussion and questionnaire. Result showed that, study programs in Community College of Blitar were less suitable with the region’s potential, as they only represented the needs for general workforce and senior secondary school graduates were more interested in continuing their study to Blitar Community College.